Stresses measurement and failure prevention of on-line natural gas transmission pipelines for compressor station on collapsible loess area in northwest China. (August 2021) - Xu, Guo-Qiang; Luo, Yun; Yao, Bin; Jiang, Wenchun
Highlights: The on-line stresses of natural gas pipelines on collapsible loess were measured. The key position for every typical cases to occur strength failure is analyzed. An improving stresses distribution method was proposed by adding support pier. The stresses of gas pipelines in the collapsible loess should be measured regularly. Abstract: There are many collapsible loess foundations in the first-line project of West-East gas pipeline of China. The collapsible loess has a great influence of the structure integrity of pipeline, especially the stress distribution. In this paper, the stresses of natural gas transmission pipelines for compressor station on collapsible loess area were measured by indentation strain method. The key position for every typical cases to occur strength failure is analyzed. A failure prevention method was also proposed. The results show that the axial stress may exceed the tensile strength induced by download bend deformation of pipelines, and becomes a potential zone to occur strength failure. An improving stresses distribution method was proposed by using added support pier below the ball valve. The axial stresses can be reduced by proposed improving method which will enhance the strength of pipelines very well. The stresses of gas pipelines in the collapsible loess should be measured regularly to avoid strength failure.